2022
DOI: 10.1177/10556656221078148
|View full text |Cite
|
Sign up to set email alerts
|

Population Prevalence and Trends of Oral Clefts in Colombia: Analysis by Departments

Abstract: Determine the population prevalence and trends of cleft lip and/or palate (CL/P) by department for Colombia in the period 2009 to 2015. Prevalence study based on Individual Registry of Health Services in general population from 2009 to 2015. All people diagnosed with CL/P were included for all ages, type of diagnosis, and any type of health services in the mentioned period. The prevalence was calculated by period and point for each year, for each department and according to the type of cleft. Stationarity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The characterization of the population object of this study showed a distribution consistent with that of previous studies carried out in the country regarding individuals with CLP [6,16,23]. Socio-demographically, individuals residing in urban areas predominated, the same as that reported by the study by González in Bogotá and Cassell in the United States [13,16].…”
Section: Discussionsupporting
confidence: 86%
“…The characterization of the population object of this study showed a distribution consistent with that of previous studies carried out in the country regarding individuals with CLP [6,16,23]. Socio-demographically, individuals residing in urban areas predominated, the same as that reported by the study by González in Bogotá and Cassell in the United States [13,16].…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, a study conducted in Colombia by Reina, Brigetty, and Salomon (2023) regarding the occurrence of orofacial clefts in Colombia revealed a total of 15,225 people with orofacial clefts, and the prevalence of cleft lip was 0.93 for every 10,000 births; the prevalence of cleft palate was 1.17 for every 10,000 births; and the prevalence of cleft lip and palate was 1.26 for every 10,000 births (unilateral cleft lip and palate prevalence was 0.83 per 10,000 births, and bilateral cleft lip and palate prevalence was 0.43 per 10,000 births) [ 27 ]. Meanwhile, in a review study performed by Shrestha et al (2023), on the occurrence of orofacial clefts in developing countries, it was revealed that the occurrence of orofacial clefts in Gujrat, India, was 0.73 in 1000 births; the occurrence of orofacial clefts in Nepal was 1.64 per live birth per year; and the occurrence of orofacial clefts in Palestinian territories was 1.01 in 1000 live births [ 28 ].…”
Section: Reviewmentioning
confidence: 99%